Comparative study of five commercial probes for the detection of Epstein-Barr virus (EBV) by in situ hybridization in cases of nodular sclerosis Hodgki's lymphoma - Suely Nonogaki; Neuza K. Shirata; Lidia M. Kimura; Juliana M. Guerra; Raphael S. S. Medeiros; Roberto Antonio P. Paes; Cristina T. Kanamura; Camila C. Oliveira; Yara de Menezes
ABSTRACT Introduction: Epstein-Barr virus (EBV) may serve as a target in therapeutic treatments, thus reliable diagnostic results are necessary. Objective: The aim of this study was to evaluate the accuracy of EBV detection by in situ hybridization (ISH) using five commercial probes in formalin-fixed and paraffin-embedded samples of nodular sclerosis Hodgkin's lymphoma (HL), and to compare the results with immunohistochemistry (IHC) and polymerase chain reaction (PCR). Material and method: Thirty samples were selected, 28 were lymph nodes, one bone marrow and one mediastinum. The following parameters were analyzed: signal intensity; proportionality of positive cells; quality of the reaction according to comfort for evaluation, sign quality and homogeneity of labeled cells; background reaction; morphology; presence of artifacts; and positivity in other non-neoplastic cells. All samples were analyzed for EBV detection using the five probes, IHC for latent membrane protein type 1 (LMP1) and PCR for Epstein Barr virus nuclear antigen 1 (EBNA1). Statistical analyses were performed with the R1 software; Fleiss' test and Cohen Kappa index of 5% were considered significant. Results: The detection by IHC-LMP1 was 26.7% (8/30) and 66.7% (20/30) by PCR-EBNA1. All probes detected EBV. Positivity was observed in 42/90 (46.7%), 38/90 (42.2%), 45/90 (50%), 27/90 (30%) and 61/90 (67.8%) for probes A, B, C, D and E, respectively. Discussion: All five probes demonstrated positivity. Conclusion: Probe E showed better rate (67.8%), sensitivity, specificity and accuracy (100%), a very good correlation among the different observers and with PCR, besides great cost-benefits relation.